Exploring the intersection of transnational, ethnic, and migration entrepreneurship. Issue 10 (26th July 2020) - Honig, Benson
ABSTRACT: In this essay, the importance of entrepreneurship is examined from multiple perspectives: Transnational, Ethnic, and Migration studies. Short historical perspectives are provided to illustrate both the universality of the immigrant entrepreneurship experience, and to highlight the need for multi-dimensional interdisciplinary study. A theoretical framework is suggested to facilitate this research, and discussions of future research opportunities are provided.